Kedudukan Pendidikan Agama Islam di Indonesia (Sebelum dan Sesudah Kemerdekaan RI) - Dwi Meutia Hasni; Haidar Putra Daulay; Lahmuddin Lahmuddin (Pusat Riset dan Inovasi Nasional, 2025)
Islamic Religious Education (PAI) in Indonesia has a long history, reflecting the dynamics of social, political, and cultural changes from the colonial era to the digital era. During the Dutch colonial era, Islamic education experienced strict restrictions, while during the Japanese occupation, it was given more flexible space even though it was full of ideological interests. After independence, PAI underwent a significant transformation with its official entry into the national education system, accompanied by the formation of the Ministry of Religion as an institution managing religious education. In the digital era, Islamic education faces new challenges in the form of unverified religious information flows, so that digital literacy becomes important in maintaining the integrity of Islamic teachings. This study uses a descriptive qualitative approach with a library research method. Data were obtained from academic literature, regulations, and official government documents and educational archives. The analysis technique used is content analysis with a focus on identifying patterns of development of Islamic Religious Education in Indonesia from the pre-independence, post-independence, to the contemporary era based on technology. This study also examines the challenges faced in each period and how Islamic education responds to these changes adaptively and contextually. The results of the study show that Islamic Religious Education continues to evolve both in terms of policy and pedagogical approach. From traditional forms such as Islamic boarding schools that focus on teaching classical books, to a formal education system based on the national curriculum, and now towards digital technology-based innovation that supports reflective and contextual learning. Thus, Islamic Religious Education in Indonesia shows its resilience as an important instrument in the formation of relevant Islamic character and identity amidst the challenges of the times.